b) 11.(x – 15) = 132
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow x-15=132:11\Leftrightarrow x-15=12\Leftrightarrow x=12+15=27\)
\(\Leftrightarrow x=15-20\Leftrightarrow x=-5\)
Ta có : 3(2x - 4) + 11 = -11
=> 3(2x - 4) = 0
Mà 3 khác 0
Nên : 2x - 4 = 0
=> 2x = 4
=> x = 2
a) \(\dfrac{x}{15}=3\Rightarrow x:15=3\Rightarrow x=3\cdot15\Rightarrow x=45\)
Vậy x = 45
b) \(\dfrac{132}{x}=11\Rightarrow132:x=11\Rightarrow x=\dfrac{132}{11}\Rightarrow x=12\)
Vậy x = 12
a) \(\dfrac{x}{15}=3\Rightarrow x=45\)
b) \(\dfrac{132}{x}=11\Rightarrow x=12\)
1)
a) 2x + 5 = 3⁴ : 3²
2x + 5 = 3²
2x + 5 = 9
2x = 9 - 5
2x = 4
x = 4 : 2
x = 2
b) (3x - 24).73 = 2.74
(3x - 24).73 = 148
3x - 24 = 148/73
3x = 148/73 + 24
3x = 1900/73
x = 1900/73 : 3
x = 1900/219
c) [3.(42 - x)] + 15 = 23.3
126 - 3x + 15 = 69
141 - 3x = 69
3x = 141 - 69
3x = 72
x = 72 : 3
x = 24
d) 126 + (132 - x) = 300
132 - x = 300 - 126
132 - x = 174
x = 132 - 174
x = -42
2)
a) 120 - (x + 55) = 60
x + 55 = 120 - 60
x + 155 = 60
x = 60 - 55
x = 5
b) (7x - 11).3 = 25.52 + 200
(7x - 11).3 = 1500
7x - 11 = 1500 : 3
7x - 11 = 500
7x = 500 + 11
7x = 511
x = 511 : 7
x = 73
c) 2x + 2x + 4 = 544
4x = 544 - 4
4x = 540
x = 540 : 4
x = 135
(x-7).(2x-8)=0
suy ra :(x-7)=0 suy ra x=7
2x-8=0 suy ra x=4
Câu b:
( x-40) .15 =15.3
(x-40) .15=45
(x-40) = 45:15
x-40 = 3
x=43
Bài 1: Tìm x biết:
a ) (x-7).(2x-8)=0
=>x-7=0 hoặc 2x-8=0
=>x=7 hoặc x=4
b) (x-40).15=15.3
=>(x-40).15=45
=>x-40=45:15
=>x-40=3
=>x=3+40
=>x=43
a)12 x 11 + 21 x 11 x 11 + 11 x 33
= ( 12 x 11 ) + ( 21 x 11 x 11 ) + ( 11 x 33 )
= 132+2541+363132+2541+363
= 30363036
b)132x11-11x32-54x11
= ( 132 x 11 ) - ( 11 x 32 ) - ( 54 x 11 )
=1452−352−594=1452−352−594
= 506506
\(a,=11\times\left(12+21+33\right)=11\times66=726\\ b,=11\times\left(132-32-54\right)=11\times46=506\\ c,=11\times\left(245+365\right)=11\times610=6710\\ d,=75\times\left(78+89+123\right)=75\times290=21750\\ e,=\left(2\times50\right)\times\left(250\times8\right)=100\times2000=200000\\ g,=1994\times\left(867+11\right)=1994\times878=1750732\)
\(11\left(x-15\right)=132\\ \Rightarrow x-15=132:11\\ \Rightarrow x-15=12\\ \Rightarrow x=12+15\\ \Rightarrow x=27\)
b) 11.(x – 15) = 132
x - 15 = 132 : 11
x - 15 = 12
x = 12 + 15
x = 27
Vậy x = 27